2020
DOI: 10.1002/lno.11588
|View full text |Cite
|
Sign up to set email alerts
|

What controls microzooplankton biomass and herbivory rate across marginal seas of China?

Abstract: Microzooplankton are the primary herbivores and nutrient regenerators in the marine food web, but their importance is often underestimated, and the quantitative relationships between environmental factors and the biomass and herbivory rate of microzooplankton remain obscure. To fill this gap, we conducted 224 dilution experiments to measure microzooplankton biomass and herbivory rate across a vast area of the marginal seas of China. To gain the potential mechanisms controlling microzooplankton herbivory, we al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
10
1
Order By: Relevance
“…In addition, we found that even within the same biome (i.e., polar), rising temperature can exert a dual effect, accentuating or reducing grazing pressure. These patterns differ from predictions by MTE ( Brown et al, 2004 ; Bruno et al, 2015 ) and field observations supporting an increased grazing pressure with rising temperature ( O’Connor et al, 2009 ; Chen et al, 2012 ; Carr et al, 2018 ; Liu et al, 2021a , b ). By contrast, our results align with experimental evidence showing a negative relationship between temperature and grazing pressure ( Menden-Deuer et al, 2018 ; Liu et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, we found that even within the same biome (i.e., polar), rising temperature can exert a dual effect, accentuating or reducing grazing pressure. These patterns differ from predictions by MTE ( Brown et al, 2004 ; Bruno et al, 2015 ) and field observations supporting an increased grazing pressure with rising temperature ( O’Connor et al, 2009 ; Chen et al, 2012 ; Carr et al, 2018 ; Liu et al, 2021a , b ). By contrast, our results align with experimental evidence showing a negative relationship between temperature and grazing pressure ( Menden-Deuer et al, 2018 ; Liu et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 92%
“…A superlinear decrease in grazing rates at low prey concentration has been observed in the lab studies of aquatic vertebrates and invertebrates and in theoretical studies (Real, 1977;Barrios-O'Neill et al, 2016). In the China Seas, the microzooplankton grazing rates are best described by a Holling type III functional response (Liu et al, 2021), providing evidence for the applicability of this functional response to whole populations, at least in the low and midlatitudes. Similarly, copepods go into diapause in the wintertime (Baumgartner and Tarrant, 2017), and this effectively reduces grazing pressure during winter; however, microzooplankton account for the majority of phytoplankton mortality in the ocean (Landry and Calbet, 2004).…”
Section: Discussionmentioning
confidence: 77%
“…7). This pattern can be explained by the increasing part of the Holling III function that is unimodal with a peak at low prey concentrations (Liu et al 2021). Furthermore, it is also likely due to a shift of community composition toward more active grazers when Chl a increased.…”
Section: Discussionmentioning
confidence: 99%